SOLUSI PERIODIK DARI PERSAMAAN KORTEWEG de VRIES (KdV) DENGAN OPERATOR BILINIER HIROTA - Rubiyanti, Sri; Sutimin, Sutimin (JURNAL SAINS DAN MATEMATIKA, 2010)
Abstract. Hirota bilinear operator (Hirota Method) is proposed to directly construct periodic wave solutions from Korteweg de Vries (KdV) equation. This solution can be expressed in terms of Jacobi Theta 4 (Θ4) functions, with dispersion relation yielded from degradation of biliear equation. Then, sinusoidal wave, Solitary, and Cnoidal can be reduced from this solution to asses certain of nome (q).Key words: Hirota Bilinear operator, Korteweg de Vries (KdV) equation, periodic profil gelombang khusus seperti gelombangCnoidal dan Solitary.Permalink : http://ejournal.undip.ac.id/index.php/sm/article/view/2962